Molecular Detection and Characterization of Coronaviruses in Migratory Ducks from Portugal Show the Circulation of Gammacoronavirus and Deltacoronavirus - Mahima Hemnani; David Rodrigues; Nuno Santos; Sergio Santos-Silva; Maria Ester Figueiredo; Pedro Henriques; Joana Ferreira-e-Silva; Hugo Rebelo; Patricia Poeta; Gertrude Thompson; João R. Mesquita (Animals, 2022)
Coronaviruses (CoVs) are part of the Coronaviridae family, and the genera Gamma (γ) and Delta (δ) are found mostly in birds. Migratory birds have an enormous potential for dispersing pathogenic microorganisms. Ducks (order Anseriformes) can host CoVs from birds, with pathogenic expression and high economic impact. This study aimed to identify and characterize the diversity of CoVs in migratory ducks from Portugal. Duck stool samples were collected using cloacal swabs from 72 individuals (Anas platyrhynchos, Anas acuta, and Anas crecca). Among the 72 samples tested, 24 showed amplicons of the expected size. Twenty-three were characterized as Gammacoronavirus and one as Deltacoronavirus (accession numbers ON368935-ON368954; ON721380-ON721383). The Gammacoronaviruses sequences showed greater similarities to those obtained in ducks (Anas platyrhynchos) from Finland and Poland, Anas crecca duck from the USA, and mute swans from Poland. Birds can occupy many habitats and therefore play diverse ecological roles in various ecosystems, especially given their ability to migrate exceptional distances, facilitating the dispersal of microorganisms with animal and/or human impact. There are a considerable number of studies that have detected CoVs in ducks, but none in Portugal. The present study assessed the circulation of CoVs in wild ducks from Portugal, being the first description of CoVs for these animals in Portugal.